Numerical investigation on the performance and detection of an industrial-sized planar solid oxide fuel cell with fuel gas leakage. (1st March 2021) - Tanaka, T.; Inui, Y.; Pongratz, G.; Subotić, V.; Hochenauer, C.
Abstract: The authors developed a simulation program for a single cell of industrial-sized planar solid oxide fuel cell (SOFC) with a scandia-ceria-stabilized-zirconia (10Sc1CeSZ) electrolyte fed with hydrogen fuel gas, to investigate its operating characteristics under fuel gas leakage conditions. Firstly, the numerical and corresponding experimental results were compared under conditions with no fuel gas leakage. The results confirmed the sufficient validity of the developed simulation program. Next, using the program, simulations involving fuel gas leakage on both sides of the SOFC were carried out. It was found that fuel gas leakage alters the stream of the fuel gas and induces a serious shortage of fuel gas in the downstream area of both side channels. This leads to a significant reduction in the local electromotive force and the appearance of regions where local electrolysis of water vapor occurs, in the downstream area on both sides. The effect of fuel gas leakage on the single cell voltage and the differential resistance was also investigated. It was revealed that the fuel gas leakage cannot be detected by only measuring the single cell voltage. On the other hand, the fuel gas leakage can be detected at an early stage, when only several percent of its inlet flow rate leaks, by measuring the differential resistance under a high fuel utilization rate condition of about 90 % and above. Based on this result, the authors proposed to employ the differential resistance, instead of the single cell voltage, as an evaluation index to detect the fuel gas leakage.